Halogen-bonding-induced diverse aggregation of 4,5-diiodo-1,2,3-triazolium salts with different anions - Xu, Xingyu; Huang, Shiqing; Zhang, Zengyu; Cao, Lei; Yan, Xiaoyu (Beilstein Journal of Organic Chemistry, 2020)
The synthesis of 4,5-diiodo-1,3-dimesityl-1,2,3-triazolium salts with different anions have been developed. These triazolium salts show diverse aggregation via halogen bonding between C–I bonds and anions. Triazolium with halide anions exists as a tetramer with saddle conformation. Triazolium tetrafluoroborate exists as a trimer with Chinese lantern shape conformation. Triazolium trifluoroacetate and acetate exist as dimers, respectively, while the former shows boat conformation and the latter forms rectangle conformation. Triazolium salts form a linear polymer with polyiodide.
Keywords: aggregation; 4,5-diiodo-1,2,3-triazolium salts; halogen bond; non-covalent interaction